Might macronutrient requirements influence grizzly bear–human conflict? Insights from nutritional geometry. Issue 1 (2nd February 2016) - Coogan, Sean C. P.; Raubenheimer, David
Abstract: Knowledge of carnivore nutritional requirements offers a potentially powerful aid for conservation and management strategies, yet has received little attention. We discuss how nutritional ecology, nutritional geometry, and the concept of macronutrient (protein, lipid, and carbohydrate) balance can be used to further our understanding of behavioral regulatory mechanisms that may influence food‐related human–wildlife conflict, focusing on North American grizzly bears ( Ursus arctos ). We propose that the macronutrient preferences of omnivorous grizzly bears are a strong driver of their conflict with humans due to nutrient‐specific foraging behavior, which we predict will be particularly noticeable during periods in which "key" natural foods high in lipid or carbohydrate are limiting. We demonstrate how nutritional geometry can be used to investigate the concept of nutrient balance by integrating recent research on the macronutrient selection of the grizzly bear with nutritional estimates of potentially consumed anthropogenic foods. Our geometric analysis utilizing right‐angled mixture triangles suggested that anthropogenic foods offer grizzly bears nonprotein energy sources that may allow them to optimize macronutrient intake. This macronutrient‐focused approach gives rise to fundamentally different predictions (and potentially management strategies) than the conventional food and energy‐focused approaches. This article also provides insight into food‐related conflict among other bear and carnivore species, and human–carnivore conflict more generally, by outlining a nutritionally explicit predictive framework for understanding the potentially volatile interface between anthropogenic environments and the behavior of wild animals.